Flexible endoscopic identification and catheterization of congenital H‐type tracheoesophageal fistula using a laryngeal mask. Issue 1 (10th September 2021) - He, Qiuming; Ou, Xinxu; Lin, Junhong; Wang, Zhe; Yan, Bin; Xie, Xiaoli; Yu, Jiakang; Zhong, Wei
Abstract : Endoscopy for revealing the orifice of congenital H‐type tracheoesophageal fistula (cTEF) is important for diagnostics and therapeutics. To facilitate the identification and catheterization of cTEF, we developed a new modified flexible endoscopy technique using a laryngeal mask with intermittent airflow. A retrospective case series study was conducted from April 2016 to July 2019 at a national regional children's medical center. Twelve infants with cTEF underwent this flexible endoscopy technique. The intermittent positive pressure airflow through laryngeal mask was able to reveal the orifice of cTEF easily in tracheal lumen. Under the visual flexible endoscope, cannulation with a 3‐Fr ureteral catheter in fistula was successfully used in all cases. There were no immediate or delayed complications. This case series shows that the flexible endoscopy technique is a safe, easy, and technically efficient approach for diagnosis and cannulation of cTEF.